Everyday creativity : singing goddesses in the Himalayan foothills - Narayan, Kirin (Big issues in music., 2016)
Kirin Narayan's imagination was captured the very first time that, as a girl visiting the Himalayas, she heard Kangra women join their voices together in song. Returning as an anthropologist, she became fascinated by how they spoke of singing as a form of enrichment, bringing feelings of accomplishment, companionship, happiness, and even good health--all benefits of the "everyday creativity" she explores in this book. Part ethnography, part musical discovery, part poetry, part memoir, and part unforgettable portraits of creative individuals, this unique work brings this remote region in North India alive in sight and sound while celebrating the incredible powers of music in our lives. With rare and captivating eloquence, Narayan portrays Kangra songs about difficulties on the lives of goddesses and female saints as a path to well-being. Like the intricate geometries of mandalu patterns drawn in courtyards or the subtle balance of flavors in a meal, well-crafted songs offer a variety of deeply meaningful benefits: as a way of making something of value, as a means of establishing a community of shared pleasure and skill, as a path through hardships and limitations, and as an arena of renewed possibility. Everyday Creativity makes big the small world of Kangra song and opens up new ways of thinking about what creativity is to us and why we are so compelled to engage it.